2015
DOI: 10.3844/ajassp.2015.525.532
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Converting Tropical Peat Swamp Forest into Oil Palm Plantation on Water Quality

Abstract: Peat swamp forest is a unique forest and wetlands ecosystem that recognized as one of the most important reservoir of biodiversity and water resources protection. Rapid development particularly for development, agriculture and plantation in peat swamp forest (PSF) area had given negative impacts to its ecosystem included degradation of its water quality. This study was conducted to determine water quality condition at undisturbed (natural peat swamp forest) and disturbed (converted peat swamp forest) and to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
(13 reference statements)
0
5
2
Order By: Relevance
“…Low dissolved oxygen (DO) levels in the drainage system might be due to high conductivity caused by the agricultural activity after planting with oil palm. DO value in this study was recorded lower as compared to the study conducted by Gandaseca et al (2015) at Sibu and Mukah District, Sarawak. Gandaseca et al (2015) found that rivers at newly planted oil palm plantations recorded DO values of 3.37+0.07 at Sibu and 3.86+0.10 at Tatau while at undisturbed peat swamp forest recorded 4.98+0.14 at Pandan and 5.02+0.09 at Sepadok.…”
Section: P R E S Scontrasting
confidence: 78%
“…Low dissolved oxygen (DO) levels in the drainage system might be due to high conductivity caused by the agricultural activity after planting with oil palm. DO value in this study was recorded lower as compared to the study conducted by Gandaseca et al (2015) at Sibu and Mukah District, Sarawak. Gandaseca et al (2015) found that rivers at newly planted oil palm plantations recorded DO values of 3.37+0.07 at Sibu and 3.86+0.10 at Tatau while at undisturbed peat swamp forest recorded 4.98+0.14 at Pandan and 5.02+0.09 at Sepadok.…”
Section: P R E S Scontrasting
confidence: 78%
“…Oil palm plantations are one of the most extensive agricultural crops in the tropics and consume the largest amount of commercial fertilizers in Southeast Asia (Maranguit et al 2017), but the effects on adjacent streams or rivers have not been well studied (Ah Tung et al 2009;Comte et al 2012Comte et al , 2015Gandaseca et al 2015; Table 4). Because of fertilizer use, the rivers surrounded by new oil palm plantations in Sarawak, Malaysia, had higher NH 4 + and biological and chemical oxygen demands (BOD and COD, respectively) than the controlled forest sites (Gandaseca et al 2015). The surface runoff from the mature oil palm farms of Papua New Guinea also had higher NH 4 + concentrations than the controlled sites, and the nutrient and water balance implied that a considerable amount of N was lost as deep drainage by leaching (Banabas et al 2008).…”
Section: Agriculturementioning
confidence: 99%
“…Conversely, NO 3 − may become the major fertilizerderived nutrient in regions where precipitation percolates and travels underground as groundwater with a relatively long residence time. In northern Queensland, Australia, sugarcane and banana cultivation have been the major industries over the last century, and the details have been reviewed in several articles (Furnas 2003;Brodie and Mitchell 2005;Davis et al 2016). In brief, the use of fertilizer in this region increased the NO 3 − concentration in the groundwater through nitrification (Thorburn et al 2003), and fertilizer-derived NO 3 − flowed into adjacent streams and rivers as baseflow (Mitchell et al 2001(Mitchell et al , 2009.…”
Section: Agriculturementioning
confidence: 99%
“…The riparian forest provides shade that reduces direct solar radiation on soil and water. This type of forest re-duces the fluctuation of air temperature in the canopy and understory, thus providing thermal regulation for stream water (Brauman et al, 2012;Gandaseca et al, 2015;Lorion & Kennedy, 2009;Studinski et al, 2012). Although the M treatment is also associated with loss of riparian forest, the dispersed presence of secondary forests (guamil) seems to buffer water temperature by preventing drastic increases.…”
Section: Temperaturementioning
confidence: 99%